Fisheries, fish pollution and biodiversity: choice experiments with fishermen, traders and consumers (2016)
The increasing rates of per capita consumption of fish around the world should be a matter of concern for those interested in the threats to fishing stocks, aquatic biodiversity and human health. Fish consumption has positive health benefits but also brings higher risks of intake of heavy metals for humans. This increase in the demand for fish products has also been accompanied with fishing practices that threaten biodiversity. This article aims at evaluating from an economic perspective how important are these health and biodiversity components for those in the fish value chain, from fishermen to final consumers, using an experimental approach to estimate, through conjoint valuation techniques, the economic value of these aspects in the decision making of these agents. We find that final consumers place a significant economic value to the reduction of exposure to mercury contamination in fish; we also show that consumers respond positively to an education campaign showing the effects of mercury contained in fish, and that this money value could be used to create campaigns that transmit better price signals throughout the chain value. On the other extreme, the fishermen, we find that they place a positive economic value in a reduction of contamination in their fish as well, which could be aligned with the results for consumers, creating opportunities for Pareto improving measures in the regulations and prices which could translate into lower demand for more contaminated fish.